Well-coordinated: learner-focused coordination tactics beyond the pandemergency. (21st December 2020) - Soccio, Philippa; Tregloan, Kate; Thompson, James
Abstract : Purpose: Post-pandemic education will be impacted by spatial and technological shockwaves, alongside other areas of society. Significant expansion of online learning will build on skills developed by educators and students in this tumultuous time, and in response to emerging challenges and structural transformations. This paper explores an oft-overlooked skill that underpins contemporary teaching, and posits that "coordination" will find its way to the centre of this new online world. The paper presents research investigating the translation of tactics for good subject coordination to an online context. Design/methodology/approach: The authors reviewed academic literature that explored coordination in higher education settings, and recent grey literature identifying expected changes to post-pandemic university learning. The authors developed a survey instrument to investigate the translation of previously identified characteristics of good coordination, and tactics to achieve them, into the pandemic-driven online learning environment. Survey analysis explored the level of difficulty reported by subject coordinators for this translation online, as well as their suggestions of additional tactics or concerns. Findings: While the low number of respondents limits these conclusions, initial analysis suggests that the identified Tactics for Coordination can be applied with relative ease to online learning environments. At the same time, the expected burgeoning of online education identified an expected increase in demand for these skills. Originality/value: The authors identified a lack of literature addressing subject coordination as a key skill, or evaluating coordination tactics, as well as a lack of resources for focused skill development. This paper addresses this gap, and prompts further and urgent response.